Development on CD-ROM - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The International Development Research Centre (IDRC) is collecting material on development activities from as many sources as possible and publishing them on CD-ROM. Two editions (1992 and 1993) have been produced. The first, on Development...